The Effect of Spark Activity on Growth Hormone Level and Motor Skills in 4-7-Year-Old Boys with Attention Deficit / Hyperactivity Disorder - Farnaz Torabi; Azar Aghayari; Shaghayegh Baradaran Moti (University of Tehran, 2019)
The aim of this study was to investigate the effect of Spark activity on growth hormone level and motor skills in 4-7-year-old boys with attention deficit / hyperactivity disorder. In this quasi-experiments study, 20 children with attention deficit/hyperactivity disorder (ADHD) were selected by multi-stage cluster sampling method from kindergartens of districts 2 and 5 of Tehran city. Then, subjects were randomly assigned to two groups: control (n=10) and experimental (n=10). The experimental group received Spark activity for 24 sessions and the control group performed their daily activities during this period. Blood samples were collected from the subjects before and after the intervention to measure the amount of growth hormone. Bruininks-Oseretsky test was used to assess motor skills. Data were analyzed using paired t test and covariance at a significance level of P<0.05. There was a significant difference between experimental and control groups in the scores of fine and gross motor skills, which were higher in the experimental group than in the control group (P=0.001). There were no significant differences in growth hormone level between the two groups (P=0.399). Based on these results, it can be concluded that one period of Spark activity can play an effective role in improving motor skills and this improvement is not associated with the level of growth hormone.